Proteomic analysis of Plasmodium falciparum parasites from patients with cerebral and uncomplicated malaria - Bertin, Gwladys I. (Sci Rep, 2016)
Plasmodium falciparum is responsible of severe malaria, including cerebral malaria (CM). During its intra-erythrocytic maturation, parasite-derived proteins are expressed, exported and presented at the infected erythrocyte membrane. To identify new CM-specific parasite membrane proteins, we conducted a mass spectrometry-based proteomic study and compared the protein expression profiles between 9 CM and 10 uncomplicated malaria (UM) samples. Among the 1097 Plasmodium proteins identified, we focused on the 499 membrane-associated and hypothetical proteins for comparative analysis. Filter-based feature selection methods combined with supervised data analysis identified a subset of 29 proteins distinguishing CM and UM samples with high classification accuracy. A hierarchical clustering analysis of these 29 proteins based on the similarity of their expression profiles revealed two clusters of 15 and 14 proteins, respectively under- and over-expressed in CM. Among the over-expressed proteins, the MESA protein is expressed at the erythrocyte membrane, involved in proteins trafficking and in the export of variant surface antigens (VSAs), but without antigenic function. Antigen 332 protein is exported at the erythrocyte, also involved in protein trafficking and in VSAs export, and exposed to the immune system. Our proteomics data demonstrate an association of selected proteins in the pathophysiology of CM.